(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human factor is of incomparable significance in any example of economic development. More there are the agricultural laborers of India, the nation’s biggest sloppy area containing the poorest workers, drudging on the bright fields of India. The majority of them hail from the socially disadvantaged segments of our general public and countless keep on living under the poverty condition. Agriculture assumes a huge job in the economic development of India. It is the foundation of rural India and it is the biggest segment of the nation’s economic movement. It gives livelihood to 60 percent of the all-out populace and gives employment to 58.4 percent of nation’s workforce. It is the single biggest endeavor. In this research paper we studied about the Agriculture Labor in India, its development and Economic Impact.